2017
DOI: 10.1515/rjdnmd-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Glycaemic Control in Patients with Diabetes Mellitus: A Case-Control Study

Abstract: Background and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
2
2
3
Order By: Relevance
“…This was similar to the SEARCH for diabetes in youth study which revealed worse glycemic control in T1DM youths who were underweight (<85th Percentile) or normal weight compared to obese subjects 7 ). The findings are not dissimilar to a Romanian study of 662 T1DM patients 8 which revealed that a BMI above the target (>25 kg/m 2 ) was not associated with greater odds of having an HbA1c higher than the standard (>7%) compared to individuals with normal BMI. The reason for this may be that those with a higher BMI have less severe metabolic decompensation and hence easier and less difficult to control diabetes unlike those who are underweight and have absolute loss of insulin which results in catabolic state and significant weight loss.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…This was similar to the SEARCH for diabetes in youth study which revealed worse glycemic control in T1DM youths who were underweight (<85th Percentile) or normal weight compared to obese subjects 7 ). The findings are not dissimilar to a Romanian study of 662 T1DM patients 8 which revealed that a BMI above the target (>25 kg/m 2 ) was not associated with greater odds of having an HbA1c higher than the standard (>7%) compared to individuals with normal BMI. The reason for this may be that those with a higher BMI have less severe metabolic decompensation and hence easier and less difficult to control diabetes unlike those who are underweight and have absolute loss of insulin which results in catabolic state and significant weight loss.…”
Section: Discussioncontrasting
confidence: 67%
“…The findings are not dissimilar to a Romanian study of 662 T1DM patients 8 which revealed that a BMI above the target (>25 kg/m 2 )…”
Section: Discussioncontrasting
confidence: 61%
“…Studi memperkirakan bahwa saat ini sekitar sepertiga populasi dunia kelebihan berat badan atau obesitas. 8 Beberapa penelitian bahkan menunjukkan bahwa risiko diabetes meningkat antara 4,5 dan 9% untuk setiap kilogram kenaikan berat badan. 9 Selain itu, obesitas terbukti menjadi faktor risiko independen untuk dislipidemia dan penyakit kardiovaskular dan penurunan berat badan dianggap sebagai ukuran kunci untuk manajemen DM tipe 2.…”
Section: Pendahuluanunclassified
“…The prevalence of glycaemic control of 58% obtained in this study was higher than 45% obtained by Ufuoma and colleagues in a cross-sectional study aimed at assessing the level of glyceamic control and its determinants among 200 T2DM patients attending a secondary hospital in Warri, Nigeria (23). BMI showed a statistically significant association with glycaemic control (p<0.01) mirroring the report of some authors in Saudi Arabia(16), Hawaii (24), Nigeria (23), Bulgaria (15), India (25) and Malaysia (26) but was inconsistent with some other studies in Turkey (27), Romania (28) and United States (29). The reason for this finding in this study is unclear.…”
Section: Discussionmentioning
confidence: 74%